Random Batch Particle Methods for the Homogeneous Landau Equation (Communications in Computational Physics, 2022)
We consider in this paper random batch particle methods for efficiently solving the homogeneous Landau equation in plasma physics. The methods are stochasticvariations of the particle methods proposed by Carrillo et al. [J. Comput. Phys.: X 7:100066, 2020] using the random batch strategy. The collisions only take place insidethe small but randomly selected batches so that the computational cost is reduced to $\mathcal{O}(N)$ per time step. Meanwhile, our methods can preserve the conservation of mass,momentum, energy and the decay of entropy. Several numerical examples are performed to validate our methods.